Antimicrobial Volatiles of the Insect Pathogen Metarhizium brunneum - Esam Hamid Hummadi; Yarkin Cetin; Merve Demirbek; Nadeems M. Kardar; Shazia Khan; Christopher J. Coates; Daniel C. Eastwood; Ed Dudley; Thierry Maffeis; Joel Loveridge; Tariq M. Butt (Journal of Fungi, 2022)
Fungal volatile organic compounds (VOCs) represent promising candidates for biopesticide fumigants to control crop pests and pathogens. Herein, VOCs produced using three strains of the entomopathogenic fungus Metarhizium brunneum were identified via GC-MS and screened for antimicrobial activity. The VOC profiles varied with fungal strain, development state (mycelium, spores) and culture conditions. Selected VOCs were screened against a range of rhizosphere and non-rhizosphere microbes, including three Gram-negative bacteria (Escherichia coli, Pantoea agglomerans, Pseudomonas aeruginosa), five Gram-positive bacteria (Micrococcus luteus, Staphylococcus aureus, Bacillus subtilis, B. megaterium, B. thuringiensis), two yeasts (Candida albicans, Candida glabrata) and three plant pathogenic fungi (Pythium ultimum, Botrytis cinerea, Fusarium graminearum). Microbes differed in their sensitivity to the test compounds, with 1-octen-3-ol and isovaleric acid showing broad-spectrum antimicrobial activity. Yeasts and bacteria were inhibited by the same VOCs. Cryo-SEM showed that both yeasts and bacteria underwent some form of “autolysis”, where all components of the cell, including the cell wall, disintegrated with little evidence of their presence in the clear, inhibition zone. The oomycete (P. ultimum) and ascomycete fungi (F. graminearum, B. cinerea) were sensitive to a wider range of VOCs than the bacteria, suggesting that eukaryotic microbes are the main competitors to M. brunneum in the rhizosphere. The ability to alter the VOC profile in response to nutritional cues may assist M. brunneum to survive among the roots of a wide range of plant species. Our VOC studies provided new insights as to how M. brunneum may protect plants from pathogenic microbes and correspondingly promote healthy growth.